Maternal and neonatal prognosis of unsupervised or inadequately supervised pregnancies at the Bonzola Hospital (Mbujimayi, Province of Kasai Oriental), Democratic Republic of the Congo - Bâtisseure Luyenga Kitengie; Constantine Malobo Ngiele; Yannick Salamayi Salamayi; Charlotte Kitenge Kitunga; Pascal Lutumba; Emery Luzolo Kafinga; Monizi Mawunu; Virima Mudogo; Jean-Pau; Basua Babintu Layka Mukandu (Orapuh, Inc., 2024)
Introduction The maternal and neonatal prognosis of unattended or poorly attended pregnancies refers to the expected outcomes for mothers and newborns in pregnancies where there has been inadequate or no antenatal care. This includes assessing the likelihood of complications during pregnancy, childbirth, and the postpartum period for the mother, as well as the health outcomes for the newborn, such as birth weight, APGAR score, and the presence of any neonatal complications. Purpose To assess the impact of inadequate antenatal care on maternal and neonatal outcomes, with a focus on identifying associated risk factors. Methods This case-control study involved 660 women and newborns delivered at the Bonzola maternity unit over one year. Two groups were categorized: the first group included 220 deliveries with no or poorly attended antenatal care (cases) and the second group included 440 deliveries with well-attended antenatal care (controls). Poorly attended antenatal care was defined as fewer than four visits, while well-attended care was defined as four or more visits, following WHO guidelines. Data on maternal age, parity, history of postpartum hemorrhage (PPH), APGAR score, and neonatal complications were collected. Logistic regression analysis was used to assess the association between inadequate antenatal care and maternal and neonatal outcomes. Results Poorly attended or unattended pregnancies accounted for 33.33% of cases. The absence of complications was more common in these pregnancies. Factors associated with poorly attended or unattended pregnancies included young maternal age (18 to 23 years) with an odds ratio (OR) of 2.53, 95% confidence interval (CI) [1.64-3.89], primiparity with an OR of 2.64, 95% CI [1.69-4.14], previous PPH with an OR of 2.74, 95% CI [1.44-5.19], poor APGAR score with an OR of 4.03, 95% CI [2.79-5.82], and neonatal complications with an OR of 4.00, 95% CI [2.69-5.95]. Conclusion Inadequate antenatal care hurts maternal and neonatal outcomes. Identifying barriers to quality maternal and child health services and implementing appropriate interventions at all levels of the health system are crucial for improving outcomes and saving lives.